The (cognitive) future of motor control and learning - Koester, Dirk (Frontiers in Sports and Active Living, 2023)
There is an ongoing debate whether dynamic systems theory (DST) and symbol-processing accounts (SPA), where SPA assume abstract representations and processing, are compatible. Or, alternatively, if either one is appropriate for describing and explaining motor control and the modification of motor skills. Both frameworks have their strengths and weaknesses. DST provide mechanistic explanations and take system complexity and the environment into account without reference to mental entities. System behaviour is described mathematically and considered deterministic. In contrast, SPA propose that abstract content, that is, mental representations of the (own) body, and task requirements are critically important for movement control. It is argued that a comprehensive understanding of motor control and learning cannot be achieved by either approach or by an (unaccomplished) unification of these frameworks. In this perspective article, it is argued that further effective sources of motor learning, such as emotional support and motivational guidance have the potential to improve and preserve motor skills indirectly and should, thus, be recognised. For applied work, qualitative approaches focussing on understanding the athlete and the situation might be appropriate.